Increased thickness of lumbar spine ligamentum flavum in wild-type transthyretin amyloidosis. (February 2021) - George, Keith M.; Hernandez, Nicholas S.; Breton, Jeffrey; Cooper, Baillee; Dowd, Richard S.; Nail, Jayde; Yu, Anthony; Mastroianni, Michael; Wang, Andy; Godara, Amandeep; Zhang, Diana; Arkun, Knarik; et al.
Highlights: Patients with ATTRwt amyloid have thicker ligamentum flavum (LF) on MRI. Pre-operative MRI could aid in clinical management of ATTRwt amyloid. Mechanism by which amyloid causes LF thickening remains to be understood. Abstract: Background: Wild-type transthyretin (ATTRwt) amyloid deposits have been found in the ligamentum flavum of patients undergoing surgery for spinal stenosis. The relationship between ATTRwt and ligamentum flavum thickness is unclear. We used pre-operative magnetic resonance imaging (MRI) to analyze ligamentum flavum thickness in lumbar spinal stenosis patients with and without ATTRwt amyloid. Methods: We retrospectively identified 178 patients who underwent lumbar spine surgery. Ligamentum flavum thickness of 253 specimens was measured on T2-weighted axial MRI. Amyloid presence was confirmed through Congo red staining of specimens, and ATTRwt was confirmed using mass-spectrometry and gene sequencing. Results: Twenty four of the 178 patients (13.5%) were found to have ATTRwt in the ligamentum flavum. Forty ATTRwt specimens and 213 non-ATTRwt specimens were measured. Mean ligamentum flavum thickness was 4.92 (±1.27) mm in the ATTRwt group and 4.00 (±1.21) mm in the non-ATTRwt group (p < 0.01). The ligamentum flavum was thickest at L4-L5, with a thickness of 5.15 (±1.27) mm and 4.23 (±1.29) mm in the ATTRwt and non-ATTRwt group, respectively (p = 0.007). There was a significant difference in ligamentum flavum thickness between ATTRwt and non-ATTRwt case for both patients younger than 70 years (p = 0.016) and those older than 70 years (p = 0.004). ATTRwt patients had greater ligamentum flavum thickness by 0.83 mm (95% confidence interval (CI): 0.41–1.25 mm, p < 0.001) when controlled for age and lumbar level. Conclusion: Patients with ATTRwt had thicker ligamentum flavum compared to patients without ATTRwt. Further studies are needed to investigate the pathophysiology of ATTRwt in ligamentum flavum thickening.